PENGEMBANGAN E-LKPD BERBASIS PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA INTERAKTIF UNTUK MENINGKATKAN LITERASI DIGITAL SISWA SMPN 1 MONTA - Maulana; fitrianingsih, Nur; Rahman Hakim, Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Project Based Learning (PjBL)-based Electronic Student Worksheet (E-LKPD) assisted by interactive media to improve the digital literacy of students at SMPN 1 Monta. The study was motivated by the low level of students' digital literacy, particularly in accessing, understanding, evaluating, and utilizing digital information effectively. In addition, the learning process is still dominated by conventional printed worksheets that are less interactive and have not optimally supported the development of 21st-century skills. This research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The product developed is a PjBL-based E-LKPD integrated with Canva and Liveworksheets interactive media on the topic of utilizing digital media to respond to hoax news. The research subjects were Grade VIII students of SMPN 1 Monta. Data were collected through expert validation sheets, teacher and student response questionnaires, observation sheets, and digital literacy tests. Data were analyzed using descriptive qualitative and quantitative techniques to determine the validity, practicality, and effectiveness of the developed product. The expected results indicate that the developed E-LKPD is valid, practical, and effective in improving students’ digital literacy, while also serving as an innovative digital learning resource that supports interactive, contextual, and technology-based learning.